Mapping Bubble Formation and Coalescence in a Tubular Cross-Flow Membrane Foaming System - Boxin Deng; Tessa Neef; Karin Schroën; Jolet de Ruiter (Membranes, 2021)
Membrane foaming is a promising alternative to conventional foaming methods to produce uniform bubbles. In this study, we provide a fundamental study of a cross-flow membrane foaming (CFMF) system to understand and control bubble formation for various process conditions and fluid properties. Observations with high spatial and temporal resolution allowed us to study bubble formation and bubble coalescence processes simultaneously. Bubble formation time and the snap-off bubble size (<semantics>D0</semantics>) were primarily controlled by the continuous phase flow rate (<semantics>Qc</semantics>); they decreased as <semantics>Qc</semantics> increased, from 1.64 to 0.13 ms and from 125 to 49 µm. Coalescence resulted in an increase in bubble size (<semantics>Dcoal>D0</semantics>), which can be strongly reduced by increasing either continuous phase viscosity or protein concentration—factors that only slightly influence <semantics>D0</semantics>. Particularly, in a 2.5 wt % whey protein system, coalescence could be suppressed with a coefficient of variation below 20%. The stabilizing effect is ascribed to the convective transport of proteins and the intersection of timescales (i.e., μs to ms) of bubble formation and protein adsorption. Our study provides insights into the membrane foaming process at relevant (micro-) length and time scales and paves the way for its further development and application.